Polarization reversal via a transient relaxor state in nonergodic relaxors near freezing temperature - Chang-Hyo Hong; Hanzheng Guo; Xiaoli Tan; John E. Daniels; Wook Jo (Journal of Materiomics, 2019)
Among the unresolved issues in the study of relaxor ferroelectrics is the role of freezing temperature, across which the dynamics of polarization reversal in relaxor ferroelectrics changes. The presence of this freezing temperature is best manifested by the appearance of a double polarization hysteresis loop just above the freezing temperature. Given that the polarization pinching evolving into a double hysteresis starts well below the freezing temperature, there exists a transient temperature regime between the nonergodic and the ergodic relaxor states. To clarify the role of the freezing temperature on the pinching, the polarization reversal near the freezing temperature of relaxor (Pb1-xLax)(Zr1-yTy)1-x/4O3 (PLZT) was monitored using three in situ electric field methods: electrocaloric effect, neutron diffraction, and transmission electron microscopy. We demonstrate that the pinching results from a two-step process, 1) domain detexturization in the ferroelectric state and 2) miniaturization of domains. This observation explains the recently reported gap between the depolarization temperature Td and the ferroelectric-to-relaxor transition temperature TF-R in lead-free relaxors. We further show that Td and TF-R, which have long been considered identical in lead-based relaxors, are not the same. The current study suggests that the mismatch between Td and TF-R is an inherent feature in both lead-based and lead-free relaxor ferroelectrics. Keywords: Relaxor, Nanodomains, In situ, Neutron diffraction, Transmission electron microscopy